Faktor Yang Mempengaruhi Kenaikan dan Penuruna Sisa Hasil Usaha (SHU) Koperasi Syariah - Farokhah Muzayinatun Niswah; Dina Fitrisia Septiarini (Jurnal Ekonomi Syariah Teori dan Terapan, 2017)
The pupose of this research is to determines the effects of own equity, assets and financing income as the factors of increase and decrease in cooperative surplus on KJKS Ben Iman Lamongan.The approach used in this study is the quantitative approach. Data analysis techniques used in this research is multiple linear regression analysis. The sampling method used in this study is purposive sampling, the sample is KJKS Ben Iman Lamongan. The author uses secondary data from monthly reports of balance sheet and the calculation surplus of operations of the period January 2014 to December 2016.The results of this study are own equity and assets partially no significant effect on the cooperative surplus distribution, financing income partially significant affect the cooperative surplus distribution and own equity, assets and financing income simultaneously affect the cooperative surplus distribution amounted to 93.13% while the rest 6,87% determined by othervariables.